Total Quality Management Dan Biaya Mutu: Meningkatkan Daya Saing Melalui Kualitas Produk - Ni Luh Putu Anom Pancawati (Jayapangus Press, 2022)
Increasingly competitive business competition demands innovation in the quality of products produced by companies with the aim to fulfill customer satisfaction, one of which is through Total Quality Management (TQM) techniques. The achievement of optimum company performance can be achieved by implementing Total Quality Management (TQM) properly and being able to reduce quality costs in creating quality products. This study aims to identify the relationship between Total Quality Management (TQM) and the cost of quality on product quality using a literature review. The research uses qualitative methods related to the research problem. The results showed that by implementing Total Quality Management (TQM) on an ongoing basis by involving all components of management has a direct relationship to product quality. Product quality is influenced by quality costs which consist of prevention, assessment, internal, and external failure costs. The fewer defective products produced, the higher the allocation of quality costs used by the company to produce quality products, this leads to an increase in orders or customer demand which means it will increase sales and company profits.